2016
DOI: 10.18844/gjit.v5i2.197
|View full text |Cite
|
Sign up to set email alerts
|

Online learning community software to support success in project teams

Abstract: <p>In this research we explore aspects of social interaction and community as they relate to success in project-based courses. Using specialized online community software consisting of social networking technologies and project-based wikis, project teams are able to collaborate and interact as they progress towards project milestones. Our study underscores the importance of sustained engagement as a means for fostering high levels of community and how these levels relate to project motivation and, ultima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
5
0
3
Order By: Relevance
“…Τέλος, αξίζει να σημειωθεί πως το ερωτηματολόγιο ήταν ανώνυμο, ώστε να διασφαλισθεί η αξιοπιστία και ειλικρίνεια των απαντήσεων και η συμπλήρωση του ήταν εθελοντική από τα εγγεγραμμένα μέλη του LSN. Ειδικότερα και σύμφωνα με το ερευνητικό ερώτημα και τη συμβολή του LSN στη μαθησιακή πορεία των επιμορφούμενων αποτυπώθηκαν τα παρακάτω: 1.Επικοινωνία: Παρείχε ευελιξία ως προς τον χρόνο επικοινωνίας, επιβεβαιώνοντας ανάλογα ευρήματα (Ophus &Abbitt, 2009), παρέχοντας δυνατότητες για έκφραση των απόψεων, μέσα σε ένα κλίμα συνεργασίας, χωρίς τον φόβο του λάθους, σε μια άτυπη και λιγότερο πιεσμένη ατμόσφαιρα σε σχέση με τα προγραμματισμένα δια ζώσης μαθήματα (McCarthy, 2010) και εν τέλει δημιουργώντας τις συνθήκες για μια αποτελεσματική επικοινωνία (Kan, 2011• Thoms & Eryilmaz, 2016. 2.Συνεργασία: Παρείχε στους συμμετέχοντες συνθήκες ενός κοινόχρηστου περιβάλλοντος μάθησης, επιτρέποντάς τους να δημιουργήσουν εύκολα και γρήγορα τις δικές τους ομάδες, στις οποίες επικοινωνούσαν, διαμοίραζαν υλικό, προχωρούσαν στην ανατροφοδότηση των απόψεων των μελών της ομάδας όπως συνέβη και σε προηγούμενες έρευνες (Conole & Alevizou,2010• Franklin & Harmelen, 2007.…”
Section: ερωτηματολόγιοunclassified
“…Τέλος, αξίζει να σημειωθεί πως το ερωτηματολόγιο ήταν ανώνυμο, ώστε να διασφαλισθεί η αξιοπιστία και ειλικρίνεια των απαντήσεων και η συμπλήρωση του ήταν εθελοντική από τα εγγεγραμμένα μέλη του LSN. Ειδικότερα και σύμφωνα με το ερευνητικό ερώτημα και τη συμβολή του LSN στη μαθησιακή πορεία των επιμορφούμενων αποτυπώθηκαν τα παρακάτω: 1.Επικοινωνία: Παρείχε ευελιξία ως προς τον χρόνο επικοινωνίας, επιβεβαιώνοντας ανάλογα ευρήματα (Ophus &Abbitt, 2009), παρέχοντας δυνατότητες για έκφραση των απόψεων, μέσα σε ένα κλίμα συνεργασίας, χωρίς τον φόβο του λάθους, σε μια άτυπη και λιγότερο πιεσμένη ατμόσφαιρα σε σχέση με τα προγραμματισμένα δια ζώσης μαθήματα (McCarthy, 2010) και εν τέλει δημιουργώντας τις συνθήκες για μια αποτελεσματική επικοινωνία (Kan, 2011• Thoms & Eryilmaz, 2016. 2.Συνεργασία: Παρείχε στους συμμετέχοντες συνθήκες ενός κοινόχρηστου περιβάλλοντος μάθησης, επιτρέποντάς τους να δημιουργήσουν εύκολα και γρήγορα τις δικές τους ομάδες, στις οποίες επικοινωνούσαν, διαμοίραζαν υλικό, προχωρούσαν στην ανατροφοδότηση των απόψεων των μελών της ομάδας όπως συνέβη και σε προηγούμενες έρευνες (Conole & Alevizou,2010• Franklin & Harmelen, 2007.…”
Section: ερωτηματολόγιοunclassified
“…Madge et al (2009) also report positive impact of students use of Facebook, but equally that lecturers should be careful in mixing the students' informal spaces with formal learning activities. Furthermore, according to (Thoms, 2016) the use of more recognisable systems, such as Twitter, Facebooks and Google Drive offer better opportunities to support online communities of practice, knowledge construction and learning compared to institutional systems.…”
Section: Ict In the Cdm Programme -For Courses And Project Workmentioning
confidence: 99%
“…However, as identified in Thoms et al [5,6,7], online social networking (OSN) software has shown to be more effective at replicating face-toface learning environments, resulting in higher perceived levels of interaction and community and overall levels of course satisfaction. OSN software has also shown success in academic communities by facilitating norms of reciprocity, building trust and providing new opportunities for collective action [8,9,10]. Furthermore, OSN software helps students develop shared understandings and mutual support and discussion spaces that can address problems students have with course material [11,12].…”
Section: Introductionmentioning
confidence: 99%